2014
DOI: 10.5194/amt-7-2581-2014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between CARIBIC Aerosol Samples Analysed by Accelerator-Based Methods and Optical Particle Counter Measurements

Abstract: Abstract. Inter-comparison of results from two kinds of aerosol systems in the CARIBIC (Civil Aircraft for the Regular Investigation of the atmosphere Based on a Instrument Container) passenger aircraft based observatory, operating during intercontinental flights at 9-12 km altitude, is presented. Aerosol from the lowermost stratosphere (LMS), the extra-tropical upper troposphere (UT) and the tropical mid troposphere (MT) were investigated. Aerosol particle volume concentration measured with an optical particl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
4
23
0
Order By: Relevance
“…The modeled aerosol extinction ratio peaks in the UTLS over Asia in a layer extending from 14 to 18 km, which is consistent with SAGE II observations [ Thomason and Vernier , ] and CALIPSO observations [ Vernier et al ., ]. The simulations reproduce the S/C ratio established by in situ measurements of the CARIBIC observatory [ Martinsson et al ., ] from 200 mb to 300 mb over Europe and Asia. The S/C ratio decreases from higher latitudes to lower latitudes, which possibly results in part from more organics emitted over India and China than over Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modeled aerosol extinction ratio peaks in the UTLS over Asia in a layer extending from 14 to 18 km, which is consistent with SAGE II observations [ Thomason and Vernier , ] and CALIPSO observations [ Vernier et al ., ]. The simulations reproduce the S/C ratio established by in situ measurements of the CARIBIC observatory [ Martinsson et al ., ] from 200 mb to 300 mb over Europe and Asia. The S/C ratio decreases from higher latitudes to lower latitudes, which possibly results in part from more organics emitted over India and China than over Europe.…”
Section: Discussionmentioning
confidence: 99%
“…CARIBIC (Civil Aircraft for the Regular Investigation of the atmosphere Based on a Instrument Container) provides observations of trace gases and aerosols since 1997 through intercontinental flights at 9–12 km altitude, which is at the lower edge of the ATAL [ Brenninkmeijer et al ., ]. We use CARIBIC aerosol elemental analysis data [ Martinsson et al ., ] from 2005 to 2014 collected during 330 flights from Frankfurt in Germany to East Asia (Guangzhou, China), Southeast Asia (Bangkok, Thailand), and the Indian subcontinent (Chennai, India). Detailed sampling and elemental analysis methods are described in Nguyen et al .…”
Section: Methodsmentioning
confidence: 99%
“…The inlet used in phase #1 had an estimated sampling efficiency of 90% for 0.1–1 µm particles [ Hermann et al , ]. The presently used system (phase #2) has a sampling efficiency of 60% for 5 µm particles and a high transmission (>90%) for submicron particles [ Martinsson et al , ; Rauthe‐Schöch et al , ]. A cyclone with close to 100% transmission for submicron particles [ Nguyen et al , ] and a cutoff size of 2 µm are installed to reduce the influence from larger particles.…”
Section: Methodsmentioning
confidence: 99%
“…When analyzing the first flight data it was found that high, short-time peaks in the CARIBIC OPSS particle number and mass concentrations correlated well with the occurrence of clouds (Martinsson et al, 2014;Weigelt, 2015). The latter were identified using the cloud water content measured in parallel in situ by the CARIBIC water instruments (Dyroff et al, 2014) and, when this parameter was not available, using the modeled cloud water content from KNMI (www.knmi.nl/ samenw/campaign_support/CARIBIC/index.html, accessed 1 July 2015).…”
Section: Post-flight Data Processingmentioning
confidence: 99%
“…In this study we present a new OPSS applied for regular measurements of the UT/LMS particle number size distribution on board a passenger aircraft. Particle size distributions measured by this OPSS were already used in previous studies (Rauthe-Schöch et al, 2012;Martinsson et al, 2014;Andersson et al, 2015), but here the instrument is described in detail for the first time (Sect. 2).…”
Section: Introductionmentioning
confidence: 99%